Pengembangan Model Pembelajaran Tematik Tema Pahlawanku Berbasis Inkuiri Terbimbing - Halimatus, Siti; Triwahyudianto (Jurnal Penelitian dan Pendidikan IPS, 2023)
The article is observation to implementation of learning in grade IV SD Islam Al Hikmah Gadang still uses textbooks, and simple book summaries that are not yet in the form of learning modules, so there is a need for a thematic learning module to support learning that is adapted to the theme of my hero. In developing this My Hero Theme learning module, the researcher developed a thematic learning module through a guided inquiry approach. Where this study aims to determine the feasibility and practicality of the guided inquiry based heroku theme learning module. The module was developed with the learning design of the Four-D Model device development model suggested by Thiagarajan et al. (1974). This model consists of 4 stages of development, namely Define, Design, Develop, and Disseminate or be adapted into a 4-D model, namely defining, designing, developing, and distributing. Validation test with material, language and media experts. Data collection techniques using a questionnaire. The data analysis technique used quantitative data and qualitative data. The results showed that the module was feasible to use. The results of the validity assessment were carried out to 3 experts, namely teaching materials, language, and multimedia experts with a score of 95.5% for material experts who were categorized as "Very Good", linguists got a score of 88.4% which means "Good", media/graphics expert of 88.3% which means "Good". Thus, the guided inquiry-based thematic learning module on the theme of my hero is suitable for use in the learning process.